REGULATING SUSPECT DISPLAY IN PRESS CONFERENCES: SAFEGUARDING HUMAN RIGHTS AND THE PRESUMPTION OF INNOCENCE - Adam Ilyas; Maman Sudirman (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Press conferences involving suspects are frequently justified as mechanisms for ensuring accountability within law enforcement. However, these press conferences pose significant risks to the presumption of innocence and may lead to violations of human rights. This research seeks to establish normative limitations on the conduct of press conferences to safeguard the presumption of innocence. Utilizing a normative legal methodology, this study employs statutory, case, and conceptual approaches. The findings indicate that presenting a suspect in an open press conference tends to foster a presumption of guilt within the community, often before a court has rendered a legally binding decision. Moreover, the absence of explicit regulatory guidelines generates legal uncertainty and heightens the potential for abuse of authority by law enforcement officials. Consequently, stringent regulations are imperative to ensure that press conferences are conducted only when the suspect voluntarily agrees to appear in public, free from coercion, in the presence of legal counsel, and under the supervision of an independent oversight body. Such regulations would help balance the public's right to information with the protection of the suspect’s dignity and legal rights..